Implementation of Intervention Through Range of Motion (ROM) Exercises to Overcome Physical Activity Mobility Impairment in Mrs. R in the Stroke Unit of RSD Gunung Jati, Cirebon City - Amal, Safira Melenia; Dwi, Citra Setyo; Andini , Andini; Purbasari, Dwiyanti (Department of Publication of Inspirasi Elburhani Foundation Desa. Pamokolan, Kecamatan Cihaurbeuti, Kabupaten Ciamis, Provinsi Jawa Barat, Indonesia, 2025)
Background & Objective: Non-hemorrhagic stroke is a stroke that occurs due to a blockage in the blood vessels caused by a disruption in the blood supply to the brain, resulting in the cessation of blood flow to the brain. Stroke can cause disability in one of the limbs and weakness in one of the limbs. This results in the loss of coordination and the loss of balance. Therefore, therapy is needed to improve muscle strength in stroke patients through Range of Motion interventions. This final scientific work aims to analyze nursing care for patients with physical mobility disorders. Method: The research method used is a case study. The subject in this case involves one respondent with a non-hemorrhagic stroke and physical mobility disorders who is undergoing treatment in the stroke unit at RSD Gunung Jati. Data collection was conducted using interview, observation, and documentation techniques. Result: The nursing diagnoses identified for Mrs. R included physical mobility impairment, anxiety, and acute pain. The interventions provided were based on the Indonesian Nursing Diagnosis and Intervention Standards (SDKI and SIKI) and the principles of Evidence-Based Nursing (EBN). The implementation of interventions such as mobility support, although not yet fully optimal within 3 days. Range of Motion (ROM) exercises were found to have a positive impact on improving muscle strength and joint flexibility in patients, as well as reducing stiffness and pain symptoms. Conclusion: It is recommended to implement nursing care for stroke patients by applying Evidence-Based Nursing (EBN), specifically: Range of Motion.